Financial dynamics and post-pandemic recovery of a public multidisciplinary hospital in Kazakhstan: a five-year financial case study - Maira Alimbetova; Kuralbai Kurakbayev; Zhumagali Ismailov; Rupal Najhawan; Zhanar Akimbaeva; Mairash Baimuratova; Marzhan Kassenova (Frontiers in Public Health, 2026)
Background The COVID-19 pandemic substantially affected the financial performance of healthcare organizations worldwide. However, evidence describing hospital financial dynamics during the pandemic and post-pandemic periods remains limited in Central Asia. Objective To evaluate changes in the financial indicators of a public multidisciplinary hospital in Kazakhstan during 2020–2024 using audited financial statements. Methods: A retrospective quantitative case study was conducted using audited annual financial statements of the Almaty Multidisciplinary Clinical Hospital for 2020–2024. Horizontal, vertical, ratio, and trend analyses were performed to evaluate changes in assets, liabilities, receivables, inventories, fixed assets, liquidity, and financing structure. Long-term financial dynamics were additionally assessed using the coefficient of variation (CV) and compound annual growth rate (CAGR). Results Marked changes in financial indicators were observed during the study period. Accounts receivable decreased from 463,934 thousand KZT in 2020 to 236,584 thousand KZT in 2021 before increasing to 434,491 thousand KZT in 2024. Inventories increased from 281,068 to 748,922 thousand KZT (CAGR = 27.8%). Accounts payable declined in 2021 and subsequently increased to 669,583 thousand KZT in 2024. The current liquidity ratio increased from 1.45 in 2020 to 1.76 in 2024, while the autonomy coefficient remained above 0.60 throughout the study period, indicating a consistently high proportion of equity in the hospital’s financing structure. Variability analysis showed that accounts payable exhibited the greatest dispersion (CV = 80.7%), whereas fixed assets remained the most stable financial component (CV = 6.9%). Conclusion The financial indicators demonstrated substantial variation during the pandemic years, followed by a more stable pattern after 2022. The findings show that routinely available financial indicators can be used to monitor changes in hospital financial performance during periods of major healthcare system disruption. This study provides new evidence on hospital financial dynamics from Central Asia and may inform future comparative research on healthcare financing and organizational performance.